A practical method to determine the dynamic fracture strain for the nonlinear finite element analysis of structural crashworthiness in ship–ship collisions. (19th May 2018) - Ko, Yeong Gook; Kim, Sang Jin; Sohn, Jung Min; Paik, Jeom Kee
ABSTRACT: Ship–ship collisions continue to occur regardless of efforts to prevent them. The collisions involve highly nonlinear characteristics associated with structural crashworthiness, including crushing and fracture as well as buckling and plastic collapse. When applying nonlinear finite element analysis (NLFEA) to solve these problems, a reliable critical fracture strain accounting for strain-rate effects due to collision speed must be implemented. This study proposes a practical method to estimate the dynamic fracture strain to be used for the structural crashworthiness analysis associated with the collisions. For this purpose, the strain-rate characteristics in struck ship were investigated by NLFEA, in which the striking vessel was assigned various velocities in the range of practical ship speeds. Based on computations, an empirical formula was developed to calculate the strain rate at a given collision speed, allowing for a practical estimation of the dynamic fracture strain. The formula is validated by a comparison with experiment.